Flexural Behaviors of Precast Reinforced Concrete -EPSfoam-Steel Deck Hybrid Panel - Mardiana Oesman (JACEE (Journal of Advanced Civil and Environmental Engineering), 2021)
This paper presented the flexural behavior of the newly developed hybrid panel which included the comparison of the ultimate load, load-deflection behavior, and failure modes. The experimental study was carried out on precast reinforced concrete-EPSfoam-steel deck hybrid panels (CES)  consist of three layers of material : concrete  layer is on the top, the steel deck is located on the bottom layer, and the EPS foam layer as the core. The dimensions of CES are 300 mm x 1200 mm with thickness of concrete layer and EPS foam as variables. The concrete thick were 30 mm and 40mm. The density of EPS foam was 12 kg/m3, 20 kg/m3, and 30 kg/m3. The static flexural test of CES was conducted in accordance with the ASTM C 393-00 standard for determination of flexural strength on concrete, the load was applied at third-point loading. This test was carried out with monotonic static load, deflection control using a loading frame with capacity of 10 kN. The results show that increase the thickness of the concrete layer from 30mm to 40mm with  EPSfoam density of 12 kg /m3, 20 kg/m3, and 30 kg/m3 achieved a maximum load increase of 33.51%; 46,13%; and 37.35%, respectively.